“Works like Magic”: Metaphor, Meaning, and the GUI in Snow Crash. - Kelly, Nicholas M. (Science Fiction Studies, 2018)
Computers might well be said to work “like magic.” Graphical User Interfaces (GUIs) allow computers to work predictably but inscrutably. Central to the design of GUIs are visual metaphors that help users understand the function of interface elements. In 1992, as GUIs were supplanting command-based interfaces, Snow Crash was published. In it, Neal Stephenson offers a new take on the SF/cyberpunk conceit of “cyberspace” with “the Metaverse,” a VR world Stephenson claims was inspired by real-world GUI design principles. Yet in Stephenson’s 1999 essay “In the Beginning… was the Command Line,” the author rails against metaphor-based interfaces, claiming such software separates users from total control of their systems, control that can only be achieved by learning computer code. Similarly, in Snow Crash, programming code itself is cast as magical, an analog to a pre-Babelian speech that can control human minds as if they are computers. While Stephenson’s novel does show that GUIs can constrain what users can do with their computers—as well as articulate ideas about what computers are for—it does something else. Despite its attack on GUIs, Snow Crash sees the appeal of cyberspace visions as rooted in a human desire to interact with computers in a human way. The real “magic” of making computers mean something on a human level occurs through metaphor-based mental operations which long predate computers.